Self-assembly of iron nanoclusters on the Fe3O4(111) superstructured surface - SHVETS, IGOR; MARIOTTO, GUIDO; MURPHY, SHANE (My University, 2005)
We report on the self-organized growth of a regular array of Fe nanoclusters on a nanopatterned magnetite surface. Under oxidizing preparation conditions, the s111d surface of magnetite exhibits a regular superstructure with three-fold symmetry and a 42 ? periodicity. This superstructure represents an oxygen-terminated s111d surface, which is reconstructed to form a periodically strained surface. A Fe film of 0.5 ? thickness was deposited on this surface at room temperature. Fe nanoclusters are formed on top of the surface superstructure creating a regular array with the periodicity of the superstructure. We demonstrate that at higher coverage Fe growth switches from two- to three-dimensional mode. In the areas of the surface where the strain pattern is not formed, random nucleation of Fe was observed.
PUBLISHED
Keywords: Surface Physics; thin films